Decreased butyrylcholinesterase and oxytocin levels versus increased dopamine levels in advanced Alzheimer's patients (Annals of Medical Research, 2022)
Aim: In this study, it was aimed to examine the serum levels of dopamine, oxytocin, and butyrylcholinesterase (BchE) enzyme activity in advanced Alzheimer's disease (AD).Materials and Methods: For our preliminary study, a total of 40 participants were included in the study. 20 of the participants consisted of patients and the other 20 made up the control group. In the serum samples of the patient and control group, the levels of dopamine and oxytocin were measured by Enzyme-Linked Immuno Sorbent Assay (ELISA) method, while the BchE activity was measured by the spectrophotometric method.Results: We found that serum BchE and oxytocin levels in the AD group were statistically lower than the controls (p0.05).Conclusion: Our results indicate that the decrease in BchE activity and oxytocin levels and the increase in dopamine levels may have a relationship with the progression of the disease in the AD group. However, we believe that studies are needed with larger numbers of patients with different levels of AD.
Keywords: Alzheimer; Dopamine; Oxytocin; Butyrylcholinesterase